Paraneoplastic Rheumatic Disorders - Ömer Faruk ŞENDUR, (Archives of Rheumatology, 2012)
Paraneoplastic rheumatic disorders are defined as rheumatic symptoms resulting from an underlying malignant disease, which is not directly related to a tumor or metastasis. The clinical course of the disease is generally in parallel with the underlying malignancy. Such kind of rheumatic symptoms are unresponsive to conventional treatments, while mostly improve with successful treatment of the underlying malignancy. Early diagnosis of malignancies may be possible with suspicion of paraneoplastic rheumatic disorders by physicians in such cases.